1993
DOI: 10.1007/bf02251295
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous sodium lactate decreases plasma GABA levels in man

Abstract: Gamma aminobutyric acid (GABA), an inhibitory neurotransmitter, may play an important role in anxiety. We studied changes in plasma GABA levels in nine healthy subjects before and after infusions of sodium lactate and dextrose. Plasma GABA significantly decreased during infusions of sodium lactate (109.3 +/- 4.4 versus 91.6 +/- 5.1 pmol/ml; P = 0.0001) but not during infusions of dextrose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Interestingly. Balon et al [34] recently reported that intravenous infusion of lactate pro duced a decrease in circulating plasma GABA concentra tions which are thought to reliably reflect changes in cen tral GABA metabolism. Thus, it is possible that valproate may prevent lactate induction of panic attacks by its GABAergic activity.…”
Section: Valproatementioning
confidence: 99%
“…Interestingly. Balon et al [34] recently reported that intravenous infusion of lactate pro duced a decrease in circulating plasma GABA concentra tions which are thought to reliably reflect changes in cen tral GABA metabolism. Thus, it is possible that valproate may prevent lactate induction of panic attacks by its GABAergic activity.…”
Section: Valproatementioning
confidence: 99%